Defining the Early, Mid, and Late Subsections of Sprint Acceleration in Division I Men's Soccer Players. Issue 4 (April 2019) - Bellon, Christopher R.; DeWeese, Brad H.; Sato, Kimitake; Clark, Kenneth P.; Stone, Michael H.
Abstract : Abstract: Bellon, CR, DeWeese, BH, Sato, K, Clark, KP, and Stone, MH. Defining the early, mid, and late subsections of sprint acceleration in Division I men's soccer players. J Strength Cond Res 33(4): 1001–1006, 2019—The purpose of this study was to investigate whether the acceleration phase of sprinting could be split into subphases specific to the competitive demands of a soccer match by comparing sprint metrics at various sprint distances in Division I men's soccer players. Twenty-three Division I men's soccer athletes completed 2 maximal-effort 20-m sprints from a standing start position through an optical measurement system. Sprint metrics measured included sprint velocity (SV), step length (SL), step frequency (SF), and ground contact time (GCT). Each metric was recorded at approximately 2.5, 6, and 12 m. Sprint metrics at each distance were compared using a 2-tailed, 1-way repeated-measures analysis of variance. The results indicated that SV, SL, and SF were statistically greater at 12 m in comparison with 6 m ( p < 0.001) and 2.5 m ( p < 0.001), whereas GCT was statistically shorter at 12 m compared with 6 m ( p < 0.001) and 2.5 m ( p < 0.001). In addition, sprint metrics at 6 m also displayed the same relationships when compared to 2.5 m, with SV, SL, and SF being statistically greater ( p < 0.001) at this distance, and GCT being statistically shorter ( p < 0.001) as well. These results suggest that the acceleration phase may effectively be differentiated into early, mid, and late subphases based on differences in key sprint metrics at distances of 2.5, 6, and 12 m, respectively, in Division I men's soccer athletes.